Genome sequence of the homoacetogenic bacterium Holophaga foetida type strain (TMBS4(T)) - Anderson, Iain (Michigan State University, 2012)
Holophaga foetida Liesack et al. 1995 is a member of the phylum Acidobacteria and is of interest for its ability to anaerobically degrade aromatic compounds and for its production of volatile sulfur compounds through a unique pathway. The genome of H. foetida strain TMBS4(T) is the first to be sequenced for a representative of the class Holophagae. Here we describe the features of this organism, together with the complete genome sequence (improved high quality draft), and annotation. The 4,127,237 bp long chromosome with its 3,615 protein-coding and 57 RNA genes is a part of the Genomic Encyclopedia of Bacteria and Archaea project.